Factors Contributing Students’ Speaking Anxiety - Suparlan Suparlan (Journal of Languages and Language Teaching, 2021)
Anxiety is a dimension of foreign language speaking that is heavily investigated in the EFL contexts. The anxiety in speaking needs to find out factors making students feel anxiety in speaking. This study aims to find out the factors contributing students’ speaking Anxiety in speaking at MTs. Darul Ishlah Ireng Lauq Lombok Barat. This research is classified as case study using descriptive qualitative method. The research object covers factors contributing students’ speaking anxiety. To find out the data, questionnaire and interview activities are carried out. The questionnaire is used to know the factors making students’ anxiety in speaking. The results are in the form of percentage. Meanwhile, the interview activities are oriented to strengthen the students’ responses based on the results of questionnaire. The data are then analyzed using qualitative ways. The steps of qualitative data analysis cover data condensation, data display, and conclusion drawing or verification. Based on the result of analysis, there are 10 (ten) factors contributing students’ anxiety, such as being afraid to speak in English, being afraid with teacher’s consequence, lack of self-confident, fear of being less competent than others students, embarrassment, insufficient preparation, fear of making mistakes, limited vocabulary, habit in using English language, and language test. The detail explanation of the findings is elaborated in discussion part of this article.